Prevalencia de la arteriopatía periférica en pacientes diabeticos tipo 2, de la provincia de El Oro 2010 - Correa Navarrete, Laura M. (2011)
The diabetes is one of the main causes of peripheral arterial vascular disease. The objective was to determine the peripheral arterial disease prevalence in type 2 diabetic patients, in the diabetes clubs, of El Oro province, in the year 2010, using the ankle brachial index.